THE MAINSTREAMING OF THE GENDER PERSPECTIVE IN CRIMINAL AND ADMINISTRATIVE LAW: CHALLENGES FOR INCLUSIVE GOVERNANCE - DELGADO, FRANCISCO MANUEL RÍOS; VENTURA, LEYLI JENY AGUILAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study examines the integration of the gender perspective in the legal-sanctioning systems of criminal and administrative law in Spanish-speaking countries, with emphasis on the institutional context of Spain and Latin America. Using a quantitative and comparative approach, 180 judicial and administrative decisions issued between 2016 and 2023 in Spain, Chile, and Peru were analyzed. The results reveal that only 42% of criminal decisions and 27% of administrative decisions explicitly incorporate elements of analysis with a gender approach. In addition, a questionnaire applied to 45 legal operators and public officials shows a generalized technical deficit in the cross-cutting application of the gender approach. It is concluded that inclusive governance requires not only coherent regulatory frameworks, but also compliance indicators, specialized training and evaluation mechanisms with an intersectional approach.